1994
DOI: 10.1128/jb.176.7.2133-2135.1994
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of glucose uptake and phosphorylation in a glucose-negative mutant of Escherichia coli by using Zymomonas mobilis genes encoding the glucose facilitator protein and glucokinase

Abstract: Expression of the Zymomonas mobilis glf (glucose facilitator protein) and glk (glucokinase) genes in Escherichia coli ZSC113 (glucose negative) provided a new functional pathway for glucose uptake and phosphorylation. Both genes were essential for the restoration of growth in glucose minimal medium and for acid production on glucose-MacConkey agar plates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 21 publications
2
30
0
Order By: Relevance
“…Expression of glf on high-copy-number plasmids such as pZY600 and pUCBM20glf or on pZY507glf invariably led to glucose-positive derivatives of strain LR2-177, whereas ZSC112L and its ⌬pts derivative stayed negative. LR2-177/pZY507glf grew on glucose with growth rates up to 0.41 h Ϫ1 (Table 1); coexpression of glk led to enhanced growth ( of 0.53) similar to rates shown recently by another group (23).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…Expression of glf on high-copy-number plasmids such as pZY600 and pUCBM20glf or on pZY507glf invariably led to glucose-positive derivatives of strain LR2-177, whereas ZSC112L and its ⌬pts derivative stayed negative. LR2-177/pZY507glf grew on glucose with growth rates up to 0.41 h Ϫ1 (Table 1); coexpression of glk led to enhanced growth ( of 0.53) similar to rates shown recently by another group (23).…”
mentioning
confidence: 52%
“…The sequence of a presumptive glf gene from Z. mobilis was reported (6), and on the basis of sequence comparison, this open reading frame was found to be a member of a superfamily of sugar transporters from both prokaryotes and eukaryotes (for a recent review, see reference 3). Recently, it was shown that the glf plus glk genes of Z. mobilis complemented an Escherichia coli mutant strain, which was deficient in glucokinase and in glucose uptake, to growth on glucose (23). However, detailed glucose uptake studies using this heterologous system have not yet been reported, nor was the substrate range of this carrier studied further.…”
mentioning
confidence: 99%
“…The transport mechanism was not determined. It is known that in the absence of the glucose PTS, E-coli can transport glucose by the mannose-PTS system (29), but other possibilities may also exist.…”
Section: Elimination Of the Glucose Pts System Onlymentioning
confidence: 99%
“…Expression of this plasmid has been shown to allow simultaneous utilization of glucose and arabinose in PTS-negative E-coli mutants (24). Plasmid pLOI740 contains the full Z. mobilis glf-zwf-edd-glk operon and has been shown to restore glucose utilization in glucose-negative mutants of E-coli (29).…”
Section: Cloning and Expressing Transportersmentioning
confidence: 99%
See 1 more Smart Citation